MICROFOSSILS IN CHERTS FROM THE MESOPROTEROZOIC (MIDDLE RIPHEAN) DEBENGDA FORMATION, THE OLENEK UPLIFT, NORTHEASTERN SIBERIA - Sergeev V.N.; Knoll A.H.; Kolosova S.P.; Kolosov P.N. (My University, 1994)
Silicified shallow-water marine carbonate deposits of the Proterozoic Debengda Formation (the Olenek Uplift, northeastern Siberia) contain well preserved microfossils. One or two distinct assemblages consists only of filamentous Siphonophycus microfossils, which are presumably the extracellular sheaths of hormogonium cyanobacteria. The other is dominated by coccoidal microfossils, first by the entophysalidacean cyanobacterium Eoentophysalis. The coccoidal assemblage was recognized in the layered carbonate precipitate structures of a superficially stromatolite appearance. Despite its simple composition, the microfossil assemblage supports the generally accepted Mesoproterozoic (middle Riphean) age of the Debengda Formation. This conclusion corresponds to the available data on isotopic geochronology, and to the composition of columnar stromatolites from the Dehengda Formation. Both the structural features and carbon isotopic composition of its rocks are comparable to those of rocks of known Mesoproterozoic age, but differ from the characteristics of definitely Neoproterozoic deposits.
Keywords: Riphean; Mesoproterozoic; Precambrian::Proterozoic::Mesoproterozoic; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей; Докембрий::Протерозой::Мезопротерозойская